2020
DOI: 10.5041/rmmj.10413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Patterns of COVID-19 Cases through the ARIMA and Gompertz Models. Case Studies: Austria, Switzerland, and Israel

Abstract: On May 19, 2020, data confirmed that coronavirus 2019 disease (COVID-19) had spread worldwide, with more than 4.7 million infected people and more than 316,000 deaths. In this article, we carry out a comparison of the methods to calculate and forecast the growth of the pandemic using two statistical models: the autoregressive integrated moving average (ARIMA) and the Gompertz function growth model. The countries that have been chosen to verify the usefulness of these models are Austria, Switzerland, and Israel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In other words, the result of the estimation is essentially independent of the choice of M in this case. Finally, to bound the values of c 1 = 0.01 and c 2 = 0.2, we take into account the highest and the lowest values found in Spain and other countries, as it is seen in [34,35,37]. Those values are also reasonable with the observed range in Figure 1 described in [33].…”
Section: Remarksupporting
confidence: 75%
See 2 more Smart Citations
“…In other words, the result of the estimation is essentially independent of the choice of M in this case. Finally, to bound the values of c 1 = 0.01 and c 2 = 0.2, we take into account the highest and the lowest values found in Spain and other countries, as it is seen in [34,35,37]. Those values are also reasonable with the observed range in Figure 1 described in [33].…”
Section: Remarksupporting
confidence: 75%
“…Finally, for constructing the prior distribution of the parameter c we will assume to be independent of the other parameters. This fact can be empirically seen in [34,35,37] where authors describe different estimates of c in several countries. Moreover, Figure 7 described in [33] based on data from 73 countries shows a spread over more than one order of magnitude.…”
Section: The Prior Distributionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this work, Eqs. (12)(13)(14)(15) are presented as proof to demonstrate the coupling of the coefficients obtained during the learning process to the ANN model (Eq. 5), as well as illustrating that using three neurons in the hidden layer, ten coefficients are generated.…”
Section: Modeling the Cumulative Number Of Deaths With Annmentioning
confidence: 99%
“…The authors emphasize that a simple model can be effective by using only the observed data, without applying some type of external covariate. Perez et al [ 14 ] compared an autoregressive integrated moving average (ARIMA) and a Gompertz function growth model in the COVID-19 cases applied for Austria, Switzerland and Israel. The results show that both models have a correlation index higher than 0.999, predicting that the end of the pandemic is close in the three countries.…”
Section: Introductionmentioning
confidence: 99%